The future of prison visits? An autoethnographic perspective on the developments of the digitisation of prison visits during COVID-19 - Antojado, Dwayne (Journal of criminology, 2024)
This article explores the current status, evolution, and envisaged future of prison visits, analysing the shift in paradigm from traditional models to an increasingly digital format that demands specific policy amendments and fosters an empathetic approach towards incarceration. The discourse begins with an in-depth examination of the current prison visitation models, delving into the strengths, weaknesses, and potential of both in-person and video visitations. This exploration uncovers the critical shortcomings of in-person visits, such as limited accessibility due to geographical and logistical constraints, and the rising potential of video visits to bridge these gaps. Simultaneously, we highlight the challenges in implementing video visitation systems, focusing on issues such as equitable access to technology, appropriate surveillance, and privacy regulations. It underscores the need for considering both sides of the coin, i.e., the convenience and feasibility of video visits versus the potential risks to the privacy and dignity of incarcerated people and their families. The article then delves into the policy considerations necessary to ensure a smooth transition to video visitations, exploring regulatory and statutory amendments needed to safeguard incarcerated individuals' rights and ensure a more humane prison system. The analysis uncovers a pressing need for a robust framework that not only respects privacy rights and promotes familial ties but also supports an important goal of prisons – effective rehabilitation of incarcerated people. Proposing an idealised future model for prison visits, the discourse presents a hybrid approach that skilfully combines the strengths of both in-person and video connections. This innovative model reimagines the future of prison visits, suggesting a shift from punitive and impersonal methods to empathetic and relationship-focused practices that align with contemporary understandings of rehabilitation.